Building capacity for their members: What employers' organisations in South Africa need to know - P. A. Grobler; M. Kirsten; S. Wärnich (South African Journal of Business Management, 2005)
According to Chapter 2 of the Labour Relations Act 66 of 1995, employers, like trade unions, have a right to freedom of association. However, hardly any research has been conducted to establish the efficiency/effectiveness of employers' organisations. The question thus is: To what extent do members (companies) make use of the services rendered by their employers' organisations, and how satisfied are they with the service provided? From this study it is clear that a small percentage of companies avail themselves of the services of employers' organisations. Popular areas of contact appear to be human resource management, labour relations and training. A number of problems in the area of client satisfaction have been identified and recommendations are made to increase the efficiency/effectiveness of employers' organisations. It is clear that despite the limited use of their services, employers' organisations continue to fulfil a key role in the labour dispensation in South Africa.
Keywords: 650